Impact of water input on plankton temporal dynamics from a managed shallow saline lake - Alfonso, María Belén (2017)
La Salada is a shallow saline lake located in the SW of the Pampas subject to significant water management, so the primary objective was to assess whether the water input and physicochemical parameters have an impact on the plankton assemblages over a two year period (2013-dry and 2014-wet). The plankton community structure and physicochemical variables showed substantial changes over the study period. La Salada hosted a plankton community characterized by low diversity and small sized organisms. The nanoplanktonic fraction organisms (2-20 μm) dominate the phytoplankton community. Ochromonas sp. showed the maximum abundance throughout the whole study period. The zooplankton community was dominated by rotifers, with a lack of cladocerans. Halotolerant species, e.g. The rotifer Brachionus plicatilis and the cyclopod Apocyclops sp. were the main species. The seasonal temperature and conductivity dynamics influence the plankton abundance dynamics in La Salada. The increment of nutrients and decrease of conductivity caused by the water input led to an increase in plankton biomass and shaped its composition. These findings emphasize that interactions between plankton, salinity, and nutrients are sensitive to the water input and they improve the understanding of the impact of adequate management decisions.